Proviral MicroRNAs Detected in Extracellular Vesicles From Bronchoalveolar Lavage Fluid of Patients With Influenza Virus–Induced Acute Respiratory Distress Syndrome. (15th September 2018) - Scheller, Nicoletta; Herold, Susanne; Kellner, Ronny; Bertrams, Wilhelm; Jung, Anna Lena; Janga, Harshavadhan; Greulich, Timm; Schulte, Leon N; Vogelmeier, Claus F; Lohmeyer, Jürgen; Schmeck, Bernd
Abstract : MicroRNA miR-17-5p was found to be upregulated in extracellular vesicles in bronchoalveolar lavage fluid from patients with influenza virus–induced acute respiratory distress syndrome and in vesicles of infected lung epithelial cells. It downregulated the expression of the antiviral factor Mx1 and enhanced virus replication. Abstract: Influenza A virus (IAV) causes severe respiratory infections and alveolar epithelial damage resulting in acute respiratory distress syndrome (ARDS). Extracellular vesicles (EVs) have been shown to mediate cellular crosstalk in inflammation by transfer of microRNAs (miRNAs). In this study, we found significant changes in the miRNA composition of EVs in the bronchoalveolar lavage fluid from patients with IAV-induced ARDS. Among the 9 significantly deregulated microRNAs, miR-17-5p was upregulated in patients' BALF and in EVs of IAV-infected lung epithelial cells (A549). In these cells, transfer of miR-17-5p strongly downregulated expression of the antiviral factor Mx1 and significantly enhanced IAV replication.